MUSICAL INSTRUMENTS OF EAST AFRICA, 1 KENYA by Graham Hyslop, Nelson Africa Ltd, P.O.Box 73146, Nairobi, 1975, pp. viii, 64, photos, transcriptions - Kubik, Gerhard (International Library of African Music, 1975)
pages: 150
Keywords: Musical instruments; East Africa; African Music; Kenya